Photo-elicitation and Instragram as a deep learning strategy in Higher Education (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
This paper describes a teaching innovation project, developed in the higher education of the Early Childhood Education Degree at the University of Cadiz. The main objective was to apply photo-elicitation in the classroom as a technique for the construction of deep learning. There were three phases in which this project was developed: before, during and after. In the first and last phase, students were given a questionnaire to collect their opinion and experience in this project. The results indicate that developing active and participatory methodologies enhances students' learning from a practical, active and deep approach.